Bilateral Bifid Mandibular Condyle: A Case Report - Melo,Suzana Lubambo de (Sociedad Chilena de Anatomía, 2011)
The bifid mandibular condyle is an exceedingly rare anomaly, frequently diagnosed as an incidental finding in a panoramic radiograph. Its etiology and pathogenesis are unknown, though the most acceptable theory suggests that trauma is at the origin of the condition. This article reports a new case of bilateral bifid condyle in a 21-year-old female with history of trauma in childhood.